Effect of universal adhesive and silane pretreatment on bond durability of metal brackets to dental glass ceramics. (7th April 2021) - Yu, Jian; Zhang, Zhongni; Yang, Hongye; Wang, Yake; Muhetaer, Aihemaiti; Lei, Jinmei; Huang, Cui
Abstract: This study aimed to investigate the effect of universal adhesive and silane pretreatment on the bond durability of metal brackets to dental glass ceramics. Eighty lithium disilicate glass ceramic specimens were randomly assigned to one of four groups ( n  = 20) defined by the pretreatment and adhesive used: (i) Adper Single Bond 2; (ii) silane + Adper Single Bond 2; (iii) Single Bond Universal; and (iv) silane +Single Bond Universal. Maxillary central incisor metal brackets were bonded on the ceramic surfaces with resin composite. A shear bond strength test was conducted after 24 h of water storage and after 10, 000 thermocycles. Adhesive remnant index scoring and field‐emission scanning electron microscopy were performed to determine adhesives remaining on the ceramic surfaces and the ceramic ultrastructure following bracket debonding, respectively. After 10, 000 thermocycles, specimens treated with Single Bond Universal preserved an appropriate bond strength between brackets and glass ceramics and showed minimum ceramic surface damage following bracket debonding, which was not the case in the other three groups. The application of a silane‐containing universal adhesive without silane pretreatment achieves adequate durability of the bond of metal brackets to dental glass ceramics and allows safe debonding, which may aid in optimizing the effectiveness for orthodontic treatment.